ANALISIS STRATEGI PEMASARAN VAPESTORE BRAND REFRE5H DI MALL KOTA KASABLANKA MELALUI PENDEKATAN SWOT - Dwi Hendra Saputra; Sugeng Widodo (Jurnal Sinergi Manajemen, 2024)
Vapestore Brand REFRE5H, located in Mall Kota Kasablanka, is one of the vape stores trying to compete in the increasingly competitive market by introducing new products and flavor variants. This research uses a qualitative method with a descriptive approach and SWOT analysis to determine effective marketing strategies for REFRE5H. Based on the research, it is concluded that the strategy based on the SWOT matrix, Strength-Opportunity (SO) Strategies, Building Relationships and Networks, maximizing the privilege as a large company in building relationships, and comprehensive marketing strategies to increase visibility and market penetration.  Then Weakness-Opportunity (WO) Strategies, innovation and capacity improvement, focus on new flavor innovations and product capacity enhancement to address weaknesses and capitalize on existing market opportunities. Next, Strength-Threat (ST) Strategies, maintain distinctive features and affordable prices, preserve the uniqueness of REFRE5H products with Indonesian flavor variants while ensuring competitive prices to counter threats from competition and market trend changes. Therefore, Strengths-Weaknesses (SW) Strategies, REFRE5H needs to innovate new flavors and enhance product capacity so that it can be used longer by consumers. And Weakness-Threat (WT) Strategies, comprehensive promotion strategies formulate comprehensive promotion strategies to address threats from competition and market trend changes. Improve product promotion capabilities both online and offline to maintain market share. By leveraging strengths and opportunities while overcoming weaknesses and threats, REFRE5H can strengthen its position in the market and continue to grow successfully. This research not only fulfills the requirements of an academic assignment but also provides recommendations for business actors in the vape industry, particularly for the Vapestore Brand REFRE5H at Mall Kota Kasablanka